Home for Christmas - Rabe, Tish; Brannon, Tom (London A Random House Group Cpmpany, 2011)
Join the Cat's Christmas Eve Party with animal guests from all over the world! The Cat has some trouble trying to return a young reindeer home in time to help pull Santa's sleigh. Along the way, he meets a herd of elephants, a pod of dolphins and a single-minded army of Christmas Island crabs. They all show how working together is the best way to solve a problem, and that being at home for Christmas is the best place to be!
"I'm Ready for reading"
English stories
2
Keywords: English stories